Is the higher class greener? The relationship between social class and four types of pro-environmental behaviors - Lijuan Fan; Chuntian Lu; Ting Li (The Journal of Chinese Sociology)
Abstract Social stratification is a classic topic in sociology. Some studies have focused on class variations in pro-environmental behaviors (PEBs), with existing research yielding inconsistent results. This inconsistency may be due to the varying measurements of PEBs, as well as the complexity of class definitions. In this article, we focus on four types of PEBs (domestic recycling, green purchase behavior, good citizen behavior, and environmental activism) and comprehensively examine differences in these behaviors across objective classes, subjective classes, and class discordance. Using CGSS2021 data, this study finds that individuals in the lower objective class are more likely to participate in domestic recycling than those in the middle and upper classes, whereas individuals in the higher objective and subjective classes exhibit more green purchase behavior and engage in more good citizen behavior. The middle objective and subjective classes are found to be the most active group in environmental activism. Additionally, this study pioneers the exploration of the relationship between class discordance and PEBs. The results reveal that the underestimation of one’s own objective class significantly hinders participation in domestic recycling and green purchase behavior. This study highlights the importance of considering not only the different types of PEBs but also the complexity of class measurement.